2018
DOI: 10.1101/366161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term aerobic training does not improve memory functioning in relapsing remitting multiple sclerosis – a randomized controlled trial

Abstract: Background Only few aerobic exercise intervention trials specifically targeting cognitive functioning have been performed in MS. Objective and methods This randomized controlled trial aimed to determine the effects of aerobic exercise on cognition in relapsing-remitting MS. The primary outcome was verbal memory (Verbal learning and memory test, VLMT). Patients were randomized to an intervention group (IG) program or a waitlist control group (CG). Patients in the IG exercised according to an individually tailor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Based on an earlier trial (10), we conducted a pilot study for arm ergometry in pwMS. In contrast to previous center-based interventions (10,32), AMBOS aimed to establish a high-frequency home-based training. This study showed that a high frequency at home training is feasible for 3 months with a substantial number of 67 sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on an earlier trial (10), we conducted a pilot study for arm ergometry in pwMS. In contrast to previous center-based interventions (10,32), AMBOS aimed to establish a high-frequency home-based training. This study showed that a high frequency at home training is feasible for 3 months with a substantial number of 67 sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Spiroergometry results at baseline provided the anchor for the individualized training schedule. Specifically, the aerobic threshold as described earlier was determined (32). To validate the resulting training parameters, participants performed a briefing and familiarization session on the training tool Motomed (Reck, Betzenweiler, Germany) a few days later (see Figure 2).…”
Section: Intervention Group (Ig): Individually Tailored Arm Ergometry Trainingmentioning
confidence: 99%